Covid-19 and the work motivation: hotel employees based on Herzberg’s two factor-theory perspective / Lu’luwatin Rosdiana Aprilia, Sri Marini and Sari Melinda Rosalina De Vos - Aprilia, Lu’luwatin Rosdiana; Marini, Sri; De Vos, Sari Melinda Rosalina (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
The covid-19 has an impact on the lodging industry. The research goal is to recognise the demands of employees in order to successfully enhance job performance by improving their motivation during this pandemic. The study method utilised was a descriptive approach with a total sampling technique. The results demonstrate that the Motivator Factor is perceived well enough that it keeps employees motivated to work during the pandemic, and the Hygiene Factors are perceived well enough that employees are satisfied, causing their work motivation to remain high even during the pandemic.